Automated Derivation of Building Envelope Thermal Performance Based on BIM for Building Energy Analysis - Park, Chang-Young; Kim, Chang-Min; Jang, Hyang-In; Choi, Chang-Ho (International Journal of Engineering and Technology, 2019)
Building envelope performance is an important factor used to calculate the energy loads required for heating and cooling buildings. Despite the large influence that building envelope thermal performance has over the energy consumption of buildings, thermal performance evaluations are often carried out using two-dimensional CAD drawings that require much time and effort. Recently, Building Information Modeling (BIM) has been used as a tool to enhance the efficiency of manually performed building information management practices. In addition, studies in the field of energy performance evaluations that have incorporated BIM have also been conducted. In this study, a method of automatically extracting information from BIM necessary for the derivation of building envelope performance was proposed. The first step of the proposed method was to classify parts that directly or indirectly made contact with the outdoor air. The second step was to classify the parts composing the envelope to appropriately reflect the standard used for the evaluation. Third, the thermal transmittance of each component composing the building envelope was calculated. Lastly, the area of each part was calculated. A case study was performed on a multi-residential unit to verify the accuracy of the proposed method. The verification results indicated that the proposed method was applicable in practice. Further research is planned to verify the performance of the proposed method with regard to its application to various standards and types of residential buildings.
Keywords: Building Envelope; Building Information Modeling; Energy Analysis; Industrial Foundation Classes; Thermal Performance